2004
DOI: 10.1007/s10330-004-0162-y
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite Alterations on Chromosome 8 of Hepatocellular Carcinoma

Abstract: Objective: To study the features of microsatellite alterations on chromosome 8 and their association with clinicopathological characteristics of hepatocellular carcinoma (HCC). Methods: Ten highlypolymorphic microsatellite markers on chromosome 8 were selected to be detected for loss of heterozygosity (LOH), microsatellite instability (MSI) and allelic imbalance (AI) in 56 HCC using MegaBACE 500 automatic DNA analysis system. Results: LOH was found in 37 of 56 HCC (66.1%) on at least 1 locus, and the top three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
5
1
Order By: Relevance
“…However, a search for relationships between the specific regions of deletion and clinical parameters showed a significant association of loss of the 4q34-35 region with alcohol intake (p=0.005) and with high grade of differentiation (p=0.02). The study results were inconsistent with those of Bando et al (31) and Zhang et al (32).…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…However, a search for relationships between the specific regions of deletion and clinical parameters showed a significant association of loss of the 4q34-35 region with alcohol intake (p=0.005) and with high grade of differentiation (p=0.02). The study results were inconsistent with those of Bando et al (31) and Zhang et al (32).…”
Section: Discussioncontrasting
confidence: 57%
“…Zhang et al (32) detected LOH on chromosome 4q using PCR-simple sequence length polymorphism (PCR-SSLP) on 10 high-polymorphic microsatellite markers in 56 HCC and found that LOH on D4S426 (4q35), D4S1615 (4q31.1) and D4S1652 (4q34-qter) was more frequent in poorly or moderately differentiated HCC than in well-differentiated HCC.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical settings, however, microsatellite analysis may not be suitable as a standard method for differentiating between IM and MC in view of its labor intensiveness and high cost. Therefore, 13 microsatellite markers, previously proven to be representative markers of LOH and MSI were carefully selected (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). First, 9 microsatellite markers were analyzed, but DDx was achieved in only 71 cases (88.9%).…”
Section: Discussionmentioning
confidence: 99%
“…Microsatellite analysis. We examined 13 chromosomal microsatellite loci (D1S233, D1S407, D3S1539, D8S277, D8S261, D9S156, D9S254, D10S520, D13S284, D16S515, D4S1554, D17S513, and TP53) in 237 specimens (non-cancerous liver tissue, carcinoma tissue from the first hepatectomy, and carcinoma tissue from the re-hepatectomy) from 79 patients to detect loss of heterozygosity (LOH) on the chromosome arms using relatively frequent HCC loci that had been described in previous reports (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). The PCR primers were synthesised based on the genome sequences in a genome database.…”
mentioning
confidence: 99%
“…Liver cancer is not sensitive to chemotherapy and radiotherapy. For patients with early liver cancer of Ia-IIa, therapeutic resection of liver cancer is currently the preferred treatment option, 3 but the recurrence and metastasis rate after 5 years is as high as 40% to 70%. 4 Aspirin, also known as acetylsalicylic acid, has been used clinically for > 100 years.…”
mentioning
confidence: 99%